2015
DOI: 10.1155/2015/340218
|View full text |Cite
|
Sign up to set email alerts
|

MiR-183 Regulates ITGB1P Expression and Promotes Invasion of Endometrial Stromal Cells

Abstract: We applied in the previous study miRNA microarray screening analysis to identify several differentially expressed miRNAs, including miR-183 in normal, eutopic, and ectopic endometrium. Knockdown of miR-183 expression induced the invasiveness and inhibition of apoptosis in endometrial stromal cells. The current study aims to identify the miR-183 targets with relevance to cell functions in endometrial stromal cells, to verify the interaction of miR-183 with its target genes, and to confirm the role of miR-183 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 29 publications
3
25
0
Order By: Relevance
“…Several integrins, including αvβ3, αvβ5, αvβ6, α4β1, and α6β1, have been reported to mediate the attachment of endometrial cells to the mesothelium ( 4 , 34 36 ). The expression of these integrins is tightly regulated by diverse molecules, such as interleukin (IL)-1, IL-8, macrophage inhibitory factor (MiR)-183, prostaglandin E2, and a cannabinoid receptor agonist ( 7 , 9 11 , 37 , 38 ). However, despite the obvious importance of TGF-β1 in the progression of endometriosis ( 13 , 17 ), there have been no reports of the TGF-β1 function in the regulation of integrins in endometrial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several integrins, including αvβ3, αvβ5, αvβ6, α4β1, and α6β1, have been reported to mediate the attachment of endometrial cells to the mesothelium ( 4 , 34 36 ). The expression of these integrins is tightly regulated by diverse molecules, such as interleukin (IL)-1, IL-8, macrophage inhibitory factor (MiR)-183, prostaglandin E2, and a cannabinoid receptor agonist ( 7 , 9 11 , 37 , 38 ). However, despite the obvious importance of TGF-β1 in the progression of endometriosis ( 13 , 17 ), there have been no reports of the TGF-β1 function in the regulation of integrins in endometrial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Functional studies indicated that miR-183 might contribute to human endometrial stromal cell apoptosis and impose a negative regulatory impact on cell invasiveness in humans [67]. In addition, miR-21 is highly expressed in the sub-luminal ESC cells at implantation sites is regulated in active blastocysts in the mouse [68].…”
Section: Discussionmentioning
confidence: 99%
“…The expression level of hTERT was positively correlated with ITGB1 expression in clinical GC specimens, which was in accordance with the results from the proteomic analysis. Many studies have reported that ITGB1 could be regulated by microRNAs 23 24 , we then developed the hypothesis that whether hTERT could regulate ITGB1 via microRNAs.…”
Section: Discussionmentioning
confidence: 99%